Local RR Lyrae stars: native and alien - Zinn, R; Chen, X; Layden, A C; Casetti-Dinescu, D I (Monthly Notices of the Royal Astronomical Society, 2020)
Measurements of [Fe/H] and radial velocity are presented for 89 RR Lyrae (RRL) candidates within 6 kpc of the Sun. After the removal of two suspected non-RRLs, these stars were added to an existing data base, which yielded 464 RRLs with [Fe/H] on a homogeneous scale. Using data from the Gaia satellite (Data Release 2), we calculated the positions and space velocities for this sample. These data confirm the existence of a thin disc of RRL with [α/Fe] ∼ solar. The majority of the halo RRLs with large total energies have near-zero angular momenta about the Z-axis. Kinematically, these stars closely resemble the Gaia-Sausage/Gaia-Enceladus stars that others have proposed are debris from the merger of a large galaxy with the Milky Way. The metallicity and period distributions of the RRLs and their positions in the period-amplitude diagram suggest that this disrupted galaxy was as massive as the Large Magellanic Cloud and possibly greater. © 2019 The Author(s)
10 citations (Crossref) [2023-10-31] tex.ids: zinnLocalRRLyrae2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85082725399 type: Article
Keywords: Dynamics; Galaxy: formation; Galaxy: kinematics; Stars: variables: RR Lyrae; dept.phy; peer-reviewed

La Silla-QUEST RR Lyrae star survey II: the Crater II tidal streams - Coppi, P S; Zinn, R; Baltay, C; Rabinowitz, D; Girard, T; Howard, R; Ment, K; Rahman, R (Monthly Notices of the Royal Astronomical Society, 2024)
We describe photometry improvements in the La Silla-Quest RR Lyrae star (RRLS) survey that enable it to reach distances from the Sun (d⊙) ∼140 kpc. We report the results of surveying ∼300 deg2 of sky around the large, low-surface-brightness Crater II dwarf spheroidal galaxy. At d⊙ >80 kpc, we find a large overdensity of RRLS that extends beyond the traditional isophotal contours used for Crater II. The majority of these RRLS (34) have a linear distribution on the sky, extending over 15°, that runs through Crater II and is oriented along Crater II’s proper motion vector. We hypothesize that this unlikely distribution traces extended tidal streams associated with Crater II. To test this, we search for other Crater II stellar populations that should be in the streams. Using Gaia proper motion data, we isolate ≈ 17 candidate stars outside of Crater II that are consistent with being luminous stars from the Crater II Red Giant Branch (RGB). Their spatial distribution is consistent with the RRLS one. The inferred streams are long, spanning a distance range ∼80–135 kpc from the Galactic Centre. They are oriented at a relatively small-angle relative to our line of sight (∼25°), which means some stream stars are likely projected onto the main body of the galaxy. Comparing the numbers of RRLS and RGB candidate stars found in the streams to those in the main galaxy, we estimate Crater II has lost $\gtrsim 30~{{\rm per\ cent}}$ of its stellar mass.
Keywords: dept.phy; peer-reviewed